2014
DOI: 10.1016/j.jconrel.2014.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of pH-responsive nanoparticles to neural stem cells improves intratumoral therapy

Abstract: Intratumoral drug delivery is an inherently appealing approach for concentrating toxic chemotherapies at the site of action. This mode of administration is currently used in a number of clinical treatments such as neoadjuvant, adjuvant, and even standalone therapies when radiation and surgery are not possible. However, even when injected locally, it is difficult to achieve efficient distribution of chemotherapeutics throughout the tumor. This is primarily attributed to the high interstitial pressure which resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 54 publications
(54 reference statements)
0
50
0
Order By: Relevance
“…11 Drug-loaded polymeric micelles that were surface conjugated to NSCs showed increased efficacy relative to free NPs following an IT injection in a xenograft model of breast cancer. 12 Furthermore, relative to free nanorods, IT injection of gold nanorods loaded inside of the NSCs had improved distribution throughout the tumor, resulting in significantly increased tumor killing following laser application in a xenograft model of breast cancer. 13, 14 This work is part of an emerging body of literature demonstrating that many types of tumor tropic cells can be used to improve NP delivery and retention within tumors, including mesenchymal stem cells, 15 macrophages, 16 and T-cells.…”
Section: Introductionmentioning
confidence: 99%
“…11 Drug-loaded polymeric micelles that were surface conjugated to NSCs showed increased efficacy relative to free NPs following an IT injection in a xenograft model of breast cancer. 12 Furthermore, relative to free nanorods, IT injection of gold nanorods loaded inside of the NSCs had improved distribution throughout the tumor, resulting in significantly increased tumor killing following laser application in a xenograft model of breast cancer. 13, 14 This work is part of an emerging body of literature demonstrating that many types of tumor tropic cells can be used to improve NP delivery and retention within tumors, including mesenchymal stem cells, 15 macrophages, 16 and T-cells.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the NPs can be up to ∼fivefold larger than those typically used for cancer therapies, which translates into a >100‐fold increase in the loading potential of a typical small molecular weight chemotherapeutics. The utility of this approach has also been investigated in preclinical orthotopic breast and ovarian cancer settings .…”
Section: Preclinical Development Of Nscs As Therapeutic Vehiclesmentioning
confidence: 99%
“…STEM CELLS TRANSLATIONAL MEDICINE published by Wiley Periodicals, Inc. on behalf of AlphaMed Press a typical small molecular weight chemotherapeutics. The utility of this approach has also been investigated in preclinical orthotopic breast [43] and ovarian cancer settings [16].…”
Section: Nsc-mediated Nanoparticle Deliverymentioning
confidence: 99%
“…Another study by Mooney et al demonstrated that pH-responsive (poly(ethylene glycol)- poly((diisopropylamino)ethyl methacrylate) (PEG-PDPAEMA) nanoparticles containing docetaxel could be functionalized onto the surface of NSCs using biotin/avidin conjugation chemistry. Intratumoral injection of NSCs loaded with the docetaxel pH-responsive nanoparticles demonstrated activity for the drug but no efficacy study was performed [57]. Recently, Cao et al demonstrated tumor tropism through intraperitoneal injection of NSCs with either surface conjugated or internalized silica nanoparticles into a metastatic ovarian cancer model.…”
Section: Neural Stem Cellsmentioning
confidence: 99%